Architecture is a verb - Robinson, Sarah (Architect) (New York, NY : Routledge, 2021)
"Architecture is a Verb outlines an approach that shifts the fundamental premises of architectural design and practice in several important ways. First, it acknowledges the centrality of the human organism as an active participant interdependent in its environment. Second, it understands human action in terms of radical embodiment-grounding the range of human activities traditionally attributed to mind and cognition: imagining, thinking, remembering-in the body. Third, it asks what a building does-that is, extends the performative functional interpretation of design to interrogate how buildings move and in turn move us, how they shape thought and action. Finally, it is committed to articulating concrete situations by developing a taxonomy of human/building interactions. Written in engaging prose for students of architecture, interiors and urban design, as well as practising professionals, Sarah Robinson offers richly illustrated practical examples for a new generation of designers"--
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Foreword -- Preface -- Acknowledgements -- 1 Situated Poetics -- Architecture's Resistance -- The Possibility of an Integrated Approach -- Architecture Is a Verb -- Radical Embodiment -- Situated Poetics -- 2 From Vitruvius to the Resonant Body -- From Source to Subject -- Qualitative Measure -- Le Modulor -- No Such Thing as Average -- Situated Bodies -- Space as Medium -- Resonant Bodies -- Sphere Activitatis -- 3 Extended Organisms-Surrogate Bodies -- Philosophy of the Organism -- The Biological and the Physical: Where Do We Draw the Line? -- Extended Organisms -- The Primacy of Movement -- Primordial Techne -- Inhabiting-The Matrix of Habitual Action -- 4 Questioning Perception -- Umwelt and Affordances -- Niche Construction -- Neural Plasticity and Epigenetic Change -- Knowledge Is External -- Reprogramming Sensory Life -- Architectural Affordances -- 5 Constructing Consciousness -- Consciousness Is Rhythmic -- The Natural History of Consciousness -- Art Structures Consciousness -- The Future Enters Through the Work of Art -- Laminated Consciousness -- 6 Taxonomy of Interactions -- Structures of Consciousness -- Archaic Consciousness -- Magic Consciousness -- Mythical Consciousness -- Mental-Rational Consciousness -- Integral Consciousness -- 7 The Primacy of Breathing -- Affirming the Breath -- Empathy and Entrainment -- The Epistemology of the Skin -- Cultures of Breathing -- A Brief Study of Desert Thermal-Cultural Devices -- Resisting -- Touching -- Haptic Perception -- 8 Homo Faber -- Resonating -- Music: A Technology of Bonding -- Buildings as Musical Instruments -- Sound as a Building Material -- Dancing -- Kinesthetic Awareness -- Mechanisms of Mutuality -- Making -- 9 Collective Dreaming -- Imagining -- Complementarity -- Suspension -- Metaphor: Patterning Fields -- Remembering -- Storytelling -- Narrative and Self -- Empathy and Story -- 10 This Lesser, Rebellious Field -- Abstracting -- From Panoptics to Peripheral Vision -- Learning From the Japanese Garden -- Framing -- Thinking -- Improvisation -- Nature of the Medium -- The Bottom-Up/Top-Down Dialectic -- 11 The Soil of the Sensible -- Integration -- Inhabiting -- Eating -- Sleeping -- Being Bored -- Walking -- An Architecture of Moments -- Playing -- Counterforms -- Visceral Urbanism -- Healing -- 12 Fields of Care: Concluding Thoughts -- Taxonomy of Interactions Appendix -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Human factors; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / History